Biomarkers of rheumatoid arthritis-associated interstitial lung disease: a systematic review and meta-analysis - Guo, Luhan; Wang, Jun; Li, Jiansheng; Yao, Jiaheng; Zhao, Hulei (Frontiers in Immunology, 2024)
Abstract Background: Interstitial Lung Disease (ILD) represents the most common extra-articular manifestation of Rheumatoid Arthritis (RA) and is a major cause of mortality. This study aims to identify and evaluate biomarkers associated with Rheumatoid Arthritis-Associated Interstitial Lung Disease (RA-ILD). Methods: We searched PubMed, Cochrane Library, EMBASE, and Web of Science databases for studies related to biomarkers of RA-ILD up until October 7, 2023. The Newcastle-Ottawa Scale (NOS) and standards recommended by the Agency for Healthcare Research and Quality (AHRQ) were used for quality assessment, and meta-analysis was conducted using Stata18.0 software. Results: A total of 98 articles were assessed for quality, 48 of which were included in the meta-analysis. 83 studies were of high quality, and 15 were of moderate quality. The meta-analysis showed significant differences in biomarkers such as C-Reactive Protein (CRP), Erythrocyte Sedimentation Rate (ESR), Anti-Cyclic Citrullinated Peptide (anti-CCP) antibody, Rheumatoid Factor (RF), Krebs von den Lungen-6 (KL-6), Surfactant Protein D (SP-D), Carcinoembryonic Antigen (CEA), Carbohydrate Antigen 19-9 (CA19-9), Matrix Metalloproteinase-7 (MMP-7), C-X-C Motif Chemokine Ligand 10 (CXCL-10), and Neutrophil-to-Lymphocyte Ratio (NLR) between RA-ILD patients and RA patients. However, Platelet-to-Lymphocyte Ratio (Platelet-to-Lymphocyte Ratio (PLR)), Cancer Antigen 125 (Cancer Antigen 125 (CA-125)), and Cancer Antigen 153 (Cancer Antigen 153 (CA-153)) did not show significant differences between the two groups. KL-6, MMP-7, and Human Epididymis Protein 4 (HE4) are negatively correlated with lung function, and KL-6 is associated with the prognosis of RA-ILD. Conclusion: Biomarkers hold promising clinical value for prediction, diagnosis, severity assessment, and prognosis evaluation in RA-ILD. However, these findings need to be validated through multicenter, large-sample, prospective cohort studies.